Investigating Students Motivation as Autonomous Learners in English Language Acquisition: A Study on Politeknik Pelayaran Sulawesi Utara - Jeihn Novita C. Budiman; Nindy N. Ganap (Edumaspul: Jurnal Pendidikan, 2024)
This research delves into the motivations propelling cadets at Politeknik Pelayaran Sulawesi Utara as autonomous learners in the realm of English language acquisition. Employing a comprehensive questionnaire, the study explores the intricate factors influencing students' commitment and enthusiasm for independent language mastery. Results indicate a pronounced inclination among cadets to adopt autonomy both within and beyond the traditional classroom, emphasizing a proactive approach to English language learning. Motivations identified encompass the intrinsic joy derived from engaging with English instruction, coupled with the obligation inherent in the maritime context where English proficiency is imperative. Further, this present study delves into the interplay between academic success and motivation, revealing a compelling desire for high grades as a driving force. External factors, including praise and punishment, also contribute to shaping the motivational landscape. Additionally, the research uncovers supporting elements such as clear learning objectives, a passion for language acquisition, conducive learning environments, stimulating teaching materials, active participation opportunities, and collaborative interactions with study partners. This comprehensive exploration provides valuable insights into the nuanced motivations of cadets at Politeknik Pelayaran Sulawesi Utara, offering a foundation for informed educational strategies and interventions tailored to foster an environment conducive to autonomous language learning